Time Course and Clinical Implications of Development of Antibodies Against Adalimumab in Patients With Inflammatory Bowel Disease. Issue 6 (July 2016) - Steenholdt, Casper; Frederiksen, Madeline T.; Bendtzen, Klaus; Ainsworth, Mark A.; Thomsen, Ole Ø.; Brynskov, Jørn
Abstract : Background: Antibodies (Abs) against adalimumab (ADL) have been associated with low ADL levels and treatment failure. Aim: To characterize the temporal characteristics of anti-ADL Ab appearance and possible disappearance, and determine the clinical significance on drug efficacy and disease course. Methods: Cohort study including inflammatory bowel disease patients in whom anti-ADL Abs had been assessed by radioimmunoassay (RIA) and, in case of disappearance, by enzyme immunoassay, and functional reporter gene assay. Results: Anti-ADL Abs were evaluated in 133 serum samples from 72 patients. Seventeen patients (24%) tested positive after median of 194 days, interquartile range of 66 to 361. The proportion with anti-ADL Abs was 22% after 1 year, and 32% from 21 months onwards. Anti-ADL Abs generally persisted at repeat assessments during continued ADL therapy (n=8). Disappearance of anti-ADL Abs during therapy (n=3) was presumably caused by methodological biases due to detection of nonfunctional nonpersistent anti-ADL Abs by RIA, or false-negative measurement at reassessment by RIA and reporter gene assay. Anti-ADL Abs appeared pharmacologically active as judged by a median ADL concentration below limit of detection versus 7.4 μg/mL in anti-ADL Ab-negative samples ( P <0.0001). Anti-ADL Abs associated with loss of response (odds ratio estimated 67, P <0.0001), and shorter treatment duration ( P <0.0001). Conclusions: Abs against ADL appear in approximately one fourth of inflammatory bowel disease patients with decreasing frequency over time and usually within 1 year of therapy. Anti-ADL Abs generally persist during continued ADL therapy, and are associated with elimination of drug and treatment failure. Therefore, ADL cessation should be considered when anti-ADL Abs are detected and supported by clinical observations. Abstract : Supplemental Digital Content is available in the text.